Development of Accounting Information System for Matahari Store With RAD Method (Rapid Application Development) - Oematan, Virgine Widya; Chandrawati, T. Brenda; Chrismastuti, Agnes Advensia (Soegijapranata Catholic University, 2024)
Business company is a form of business in which business people purchase goods from vendors, then resell them to consumers without changing the form of the goods. Every business, be it large, medium to small businesses, requires an accounting system. From the accounting system, the owner can determine whether his business is running well or vice versa. One trading business that still does not use an accounting system is the Matahari Grocery Store. The accounting information system is needed by Toko Matahari to be able to compete with many other similar businesses. The method used in creating this accounting system is the Rapid Application Development method.